Technological resources, ICT use and schools efficiency in Latin America – Insights from OECD PISA 2018. (May 2023) - Agasisti, Tommaso; Antequera, Germán; Delprato, Marcos
Abstract: The efficiency of schools can be defined and measured as the ratio between the outputs produced (for example, achievement and competences) and the inputs utilized (human and technical resources). Technology holds the promise of increasing the efficiency of schools' operations, although empirical evidence on this is still scarce. This paper explores whether the ICT availability and use in 2757 schools from 10 Latin American countries are associated with higher efficiency, relying on PISA 2018. A method based on a double-bootstrap Data Envelopment Analysis (DEA) is employed. The results highlight that the availability of ICT is positively correlated with higher school efficiency. This evidence is relevant for policy implications in setting the post-COVID priorities for educational systems in the region. Highlights: We employ the PISA (2018) for the Latin American region and DEA. We study the impact of ICT access and its use on school efficiency in the region. We find a level of inefficiency for the region of around 25%, with a high degree dispersion. We find that the degree of access of ICT matters for efficiency more than ICT use. The impact of level of ICT use on efficiency is more nuanced varying across countries.